Miniburger - Baćić, Boris; Bertoncelj, Matjaž; Koco 1978-; Mirović, Katerina 1968-; Prassel, Igor 1971- (Stripburger c/o Strip Core, Forum Ljubljana, 2000)
The final assortment is an international dirty dozen: five Slovenian (Andrej Stular, Jure Meden, Ciril Horjak, Matej Lavrencic and DYS00), two Italian (Stefano Zattera, and Maicol and Mirco - actually a duo), two Serbian (Mr. Stocca, and Wostok and Ivana Filipovic), one Bosnian (Amir Idrizovic), one French (Pakito Bolino) mini graphic novel, and an English 12-pager (by Luke Canavan)
Offsetdruck. - The Stripburger special edition for the year 2000
Keywords: Graphzine